2015
DOI: 10.1371/journal.ppat.1005223
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of a Plant Negative-Strand RNA Virus from Cloned cDNA: Insights into Enveloped Plant Virus Movement and Morphogenesis

Abstract: Reverse genetics systems have been established for all major groups of plant DNA and positive-strand RNA viruses, and our understanding of their infection cycles and pathogenesis has benefitted enormously from use of these approaches. However, technical difficulties have heretofore hampered applications of reverse genetics to plant negative-strand RNA (NSR) viruses. Here, we report recovery of infectious virus from cloned cDNAs of a model plant NSR, Sonchus yellow net rhabdovirus (SYNV). The procedure involves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
152
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(165 citation statements)
references
References 59 publications
7
152
1
Order By: Relevance
“…Our previous studies showed that combined expression of the N, P, and L core protein in a single plasmid, when supplemented by additional amounts of L proteins (NPL + L), significantly improved SYNV rescue efficiency [16]. In our current experiments, the more desirable core protein mixture (NPL + L) also resulted in an increased infection rate in 35St-SYNV infiltrated plants (~ 20%).…”
Section: Resultssupporting
confidence: 54%
“…Our previous studies showed that combined expression of the N, P, and L core protein in a single plasmid, when supplemented by additional amounts of L proteins (NPL + L), significantly improved SYNV rescue efficiency [16]. In our current experiments, the more desirable core protein mixture (NPL + L) also resulted in an increased infection rate in 35St-SYNV infiltrated plants (~ 20%).…”
Section: Resultssupporting
confidence: 54%
“…We hypothesize that the P protein of cytorhabdoviruses has evolved to target multiple steps of the RNA silencing pathway, linked to their relative weak local RSS activity. Hence, further detailed studies should be conducted to probe the mechanism underlying the RSS activity of this protein, preferably using approaches that resemble the natural context of the virus-plant pathosystem, like the use of a reverse genetics system similar to the one recently developed for SYNV (Wang et al, 2015). leaves expressing mGFP5-ER were co-agroinfiltrated with mGFP5-ER plus either ADV P or P6.…”
Section: Discussionmentioning
confidence: 99%
“…The recent development of the first-ever reverse genetics system for a plant rhabdovirus provided a major technical breakthrough and a guide for the future study of other plant negative-sense ssRNA viruses (Ganesan et al, 2013; Wang et al, 2015; Jackson and Li, 2016). It allowed the recovery of infectious recombinant virus (rSYNV) from agroinfiltrated plants and the generation of rSYNV stably expressing a green fluorescent protein (GFP) reporter.…”
Section: Monopartite Plant Rhabdoviruses: Cyto- and Nucleorhabdovimentioning
confidence: 99%
“…It allowed the recovery of infectious recombinant virus (rSYNV) from agroinfiltrated plants and the generation of rSYNV stably expressing a green fluorescent protein (GFP) reporter. Deletion analyses of rSYNV-GFP demonstrated the involvement of the sc4 (P3) protein in cell-to-cell movement and the importance of the G protein in virion morphogenesis (Wang et al, 2015). …”
Section: Monopartite Plant Rhabdoviruses: Cyto- and Nucleorhabdovimentioning
confidence: 99%